2010
DOI: 10.1007/s11270-010-0639-y
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Sulfamethoxazole Applying UV- and VUV-Based Processes

Abstract: The efficiency of UV-and VUV-based processes (UV, VUV, UV/H 2 O 2 , and VUV/H 2 O 2 ) for removal of sulfamethoxazole (SMX) in Milli-Q water and sewage treatment plant (STP) effluent was investigated at 20°C. The investigated factors included initial pH, variety of inorganic anions (NO 3 − and HCO 3 − ), and humic acid (HA). The results showed that the degradation of SMX in Milli-Q water at both two pH (5.5 and 7.0) followed the order of VUV/H 2 O 2 > VUV > UV/H 2 O 2 > UV. All the experimental data well fitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 34 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The pKa values of SMZ, STZ and SMT were shown in Table 1. They had a cationic form at pH < pKa 1 and an anionic form at pH > pKa 2 [16,21]. These different ionic states of sulfonamides might have a considerable impact on their reactivity and light absorbing properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pKa values of SMZ, STZ and SMT were shown in Table 1. They had a cationic form at pH < pKa 1 and an anionic form at pH > pKa 2 [16,21]. These different ionic states of sulfonamides might have a considerable impact on their reactivity and light absorbing properties.…”
Section: Resultsmentioning
confidence: 99%
“…Among these AOPs, the UV/H 2 O 2 process consists of a combination of two well-known processes, direct UV photolysis and peroxidation, that lead to the generation of hydroxyl radicals, which make this process simpler and more effective for the removal of organic contaminants compared to peroxidation or photolysis respectively [14,15]. It is reported that some sulfonamides, such as sulfaquinoxaline sodium [14], sulfamethoxazole [16], sulfamethazine and sulfapyridine [17], can be efficiently removed by the UV/H 2 O 2 process, and the photochemical oxidation of a single antibiotic with a high concentration (>10 mg L −1 ) was elucidated. However, other contaminations in the water may dramatically affect the removal of the target pollutant by competitively interacting with hydroxyl radicals and photons or with each other among these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing a reactor for both the short penetrating VUV and relatively longer penetrating UV is challenging. Most of the laboratory-scale configurations, like quasi -collimated beam apparatus ( q CB) ( Baeza and Knappe, 2011 ; Duca et al., 2017 ; Fang et al., 2014 ; Feng et al., 2007 ), annular reactors ( Ngouyap Mouamfon et al., 2011 ; Zhan et al., 2021 ; Zoschke et al., 2012 ) and micro-fluidic vacuum UV reactors ( Yang et al., 2018 ) employed in VUV research have small mean reactor pathlengths that favorably uses VUV over UV. Despite extensive research published using laboratory-scale VUV reactors, there are scarce applications of VUV reported at pilot-scale ( Krakko et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These materials have been applied in the removal of recalcitrant organic matters with the combination of other AOPs process. Ngouyap et al [58] investigated the removal of SMX under UV-and VUV-based processes, reporting that complete degradation of 10 mg/L SMX was obtained. Kim et al [59] demonstrated that different removal efficiencies of SMX were obtained under lowpressure lamp UV (352 nm, 254 nm) and vacuum -UV (185 nm, 254 nm).…”
Section: Other Technologies For Antibiotics Removalmentioning
confidence: 99%